Recent Advances in the Development of Water Oxidation Electrocatalysts at Mild pH - Li, Peipei; Zhao, Runbo; Chen, Hongyu; Wang, Huanbo; Wei, Peipei; Huang, Hong; Liu, Qian; Li, Tingshuai; Shi, Xifeng; Zhang, Youyu; Liu, Meiling; Sun, Xuping (Small (Weinheim an der Bergstrasse, Germany), 2019)
Developing anodic oxygen evolution reaction (OER) electrocatalysts with high catalytic activities is of great importance for effective water splitting. Compared with the water‐oxidation electrocatalysts that are commonly utilized in alkaline conditions, the ones operating efficiently under neutral or near neutral conditions are more environmentally friendly with less corrosion issues. This review starts with a brief introduction of OER, the importance of OER in mild‐pH media, as well as the fundamentals and performance parameters of OER electrocatalysts. Then, recent progress of the rational design of electrocatalysts for OER in mild‐pH conditions is discussed. The chemical structures or components, synthetic approaches, and catalytic performances of the OER catalysts will be reviewed. Some interesting insights into the catalytic mechanism are also included and discussed. It concludes with a brief outlook on the possible remaining challenges and future trends of neutral or near‐neutral OER electrocatalysts. It hopefully provides the readers with a distinct perspective of the history, present, and future of OER electrocatalysts at mild conditions. Electrocatalytic water oxidation under environmentally‐friendly conditions has received considerable recent research attention. This paper reviews recent advances in the design and development of water oxidation electrocatalysts operating at mild pH, and current challenges and future research directions are also provided.